2020
DOI: 10.1186/s43166-020-00040-3
|View full text |Cite
|
Sign up to set email alerts
|

What is better for rotator cuff tendinopathy: dextrose prolotherapy, platelet-rich plasma, or corticosteroid injections? A randomized controlled study

Abstract: Background Rotator cuff tendinopathy (RCT) is a leading cause of shoulder pain and disability. Management is mainly conservative, but the limited ability of tendons to regenerate is the main cause of unsatisfactory results. So, we conducted our study to compare the efficacy of deep prolotherapy (glucose 25%), platelet-rich plasma (PRP), and betamethasone corticosteroid for treatment of RCT to find the most effective one based on clinical, functional, and radiological assessment. Results Regarding visual analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The baseline VAS scores along with their change from base‐line can be found in Table 4 . At short‐ and intermediate‐term follow‐up, the change from baseline was comparable between the CS and PRP groups and no difference was observed (short‐term: MD = −0.30, 95% CI: −1.40, 0.08; p = 0.59; I 2 = 89% 12 , 26 , 28 , 32 , 34 ) (Intermediate‐term: MD = 0.28, 95% CI: −0.71, 1.28; p = 0.58; I 2 = 84% 26 , 27 , 28 , 31 , 32 ). At medium‐term follow‐up, no difference in the change of VAS score from base‐line was observed between the PRP and CS groups (MD = 0.39, 95% CI: −1.84, 2.62; p = 0.73; I 2 = 97% 12 , 28 , 32 , 34 ).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The baseline VAS scores along with their change from base‐line can be found in Table 4 . At short‐ and intermediate‐term follow‐up, the change from baseline was comparable between the CS and PRP groups and no difference was observed (short‐term: MD = −0.30, 95% CI: −1.40, 0.08; p = 0.59; I 2 = 89% 12 , 26 , 28 , 32 , 34 ) (Intermediate‐term: MD = 0.28, 95% CI: −0.71, 1.28; p = 0.58; I 2 = 84% 26 , 27 , 28 , 31 , 32 ). At medium‐term follow‐up, no difference in the change of VAS score from base‐line was observed between the PRP and CS groups (MD = 0.39, 95% CI: −1.84, 2.62; p = 0.73; I 2 = 97% 12 , 28 , 32 , 34 ).…”
Section: Resultsmentioning
confidence: 95%
“…It has been demonstrated that an apheresis and buffy coat‐derived preparation achieved a higher platelet concentration owing to a possible extra centrifugation step, which in turn allows for higher growth factor levels, as opposed to a tube method preparation, which, on the other hand, showed the highest level of white blood cell contamination 55 . A handful of these studies utilized a similar protocol which involved a double centrifugation that gives rise to PRP derived from the upper plasma layer and the buffy coat (buffy‐coat derived) 25,30,31 . However, 12 prepared PRP manually using a single spin rotation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen studies [2, 4, 7, 11, 19–21, 25, 28, 35, 41, 43, 44, 46, 47, 54] compared conservative treatment using PRP injections vs corticosteroid (CS) (nine studies), saline (three), exercise (two), prolotherapy (two), physical therapy (one), dry needling (one), sodium hyaluronate (SH) (one), and lidocaine (one). Three of these studies had more than two groups: two studies had three arms (PRP, SH, and saline in one study; PRP, prolotherapy, and corticosteroids in the other); and one study had four arms (PRP, prolotherapy, corticosteroids, and lidocaine).…”
Section: Resultsmentioning
confidence: 99%
“…In this case, a meta‐analysis was not feasible due to the high heterogeneity of the included studies, nonetheless important findings could still be highlighted. With regard to functional outcomes, the majority of the retrieved studies reported conflicting results, with several advocating significant improvement over control (sometimes for just a few months), while others denied such a finding [2, 19, 25, 35, 43, 46]. These results are in line with the review of Lin et al [31], but are in contrast with the results of Xiang et al [61], who concluded in favour of statistical and clinical improvements in pain and function within 6 months of follow‐up.…”
Section: Discussionmentioning
confidence: 99%